Nanoscale origin of the crystalline-to-amorphous phase transformation and damage tolerance of Cantor alloys at cryogenic temperatures - Ji, Weiming (2022)
Based on recent experimental studies, crystalline-to-amorphous phase transformation has been proposed as a mechanism to enhance the damage tolerance of Cantor alloys at cryogenic temperatures. In this study, we provide atomistic insights, via molecular dynamics simulations, into the origin of the solid-state amorphization ahead of a crack tip, and report the deformation mechanisms contributing to cryogenic damage-tolerance. We show that the amorphization stems from the formation of multi-dislocation junctions due to the low stacking fault energy. This leads to high lattice resistance to dislocation glide and facilitates nucleation of amorphous nuclei. The deformation mechanisms in the amorphous/crystalline dual phase regions include high-density Shockley partial dislocations and multi-dislocation junctions in the crystalline region, as well as radiation-shaped shear bands and amorphous bridges in the amorphous region, which are rarely found in conventional alloys at low temperature. The amorphous bridges lead to crack shielding. Furthermore, altering the chemical composition changes the work-of-fracture and hence the damage tolerance. The Rice-criterion ductility (ratio between surface energy and unstable stacking fault energy) is an important factor affecting the degree of amorphization, which is useful for the mechanics-based design of Cantor alloys.